2013
DOI: 10.1371/journal.pone.0066924
|View full text |Cite
|
Sign up to set email alerts
|

Association between Apolipoprotein E Gene Polymorphism and the Risk of Coronary Artery Disease in Chinese Population: Evidence from a Meta-Analysis of 40 Studies

Abstract: BackgroundEpidemiological studies have evaluated the association between apolipoprotein E (ApoE) gene polymorphism and coronary artery disease (CAD) risk which developed inconsistent conclusions. To derive a more precise estimation of the relationship in Chinese population, we performed this meta-analysis.MethodsDatabases, including PubMed, EMbase, Web of Science, CBMdisc and CNKI, were searched to get the genetic association studies. Additionally, hand searching of the references of identified articles were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 16 publications
7
26
0
1
Order By: Relevance
“…Results with P values less than 0.05 are in bold font. It is well known that the APOE variant is a predictor of plasma lipid levels in cardiovascular disease (Yin et al, 2013). Therefore, we further stratified the data analysis into different lipids by rs4420638 genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Results with P values less than 0.05 are in bold font. It is well known that the APOE variant is a predictor of plasma lipid levels in cardiovascular disease (Yin et al, 2013). Therefore, we further stratified the data analysis into different lipids by rs4420638 genotype.…”
Section: Resultsmentioning
confidence: 99%
“…Although several recent meta-analyses explored the genetic risk of APOE polymorphisms in CAD [14][15][16], our analysis was the first comprehensive assessment in PCAD. Merging the data of all eligible publications revealed that subjects with the ε4 allele conferred 62% more predisposition to PCAD, while ε4 carriers had 65% higher risk for PCAD.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis conducted by Hong Xu found that the ε2 allele in APOE decreased the prevalence of myocardial infarction while the ε4 allele increased the incidence [14]. Two other meta-analyses conducted in the Chinese population also found a high risk of the ε4 allele for CAD [15,16]. However, no meta-analysis explored the genetic risk of APOE in PCAD.…”
Section: Introductionmentioning
confidence: 99%
“…La presencia del alelo ε4 se considera un factor de riesgo genético para la aparición de enfermedades cardiovasculares, como el infarto de miocardio, y de la enfermedad de Alzheimer (23)(24)(25), por lo que su estudio puede servir de tamización inicial en los programas de prevención de las hiperlipidemias y de la enfermedad de Alzheimer cuando su frecuencia sea muy significativa en las poblaciones estudiadas.…”
Section: Alelo ε4unclassified